2020
DOI: 10.1016/j.applthermaleng.2020.115898
|View full text |Cite
|
Sign up to set email alerts
|

Parametric study on melting process of a shell-and-tube latent thermal energy storage under fluctuating thermal conditions

Abstract: Xiaoli (2020) 'Parametric study on melting process of a shell-and-tube latent thermal energy storage under uctuating thermal conditions.', Applied thermal engineering., 180 . p. 115898.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Milliozi et al 39 also used this SA with NaNO 3 that improved thermal capacity and thermal diffusivity. Li et al 54 used alumina with compound salt with composition LiNO 3 ‐KCl‐NaNO 3 to have transient study in variable load condition and obtained a decreasing trend in heat storage capacity and increasing trend in thermal conductivity and heat transfer coefficient with increasing period of amplitude. Bonk et al 55 used industrial waste material alfer rock (Fe 2 O 3 ) with NaNO 3 ‐KNO 3 mixture that showed formation of Na 2 Fe 2 O 3 by showing its excellent compatibility to sustain the corrosiveness.…”
Section: Performance Enhancement Methodologymentioning
confidence: 99%
“…Milliozi et al 39 also used this SA with NaNO 3 that improved thermal capacity and thermal diffusivity. Li et al 54 used alumina with compound salt with composition LiNO 3 ‐KCl‐NaNO 3 to have transient study in variable load condition and obtained a decreasing trend in heat storage capacity and increasing trend in thermal conductivity and heat transfer coefficient with increasing period of amplitude. Bonk et al 55 used industrial waste material alfer rock (Fe 2 O 3 ) with NaNO 3 ‐KNO 3 mixture that showed formation of Na 2 Fe 2 O 3 by showing its excellent compatibility to sustain the corrosiveness.…”
Section: Performance Enhancement Methodologymentioning
confidence: 99%
“…The results showed that fluctuating heat flux could reduce the final average temperature and melting time of PCM compared with steady-state heat boundary. Li et al [26,27] investigated the dynamic heat transfer characteristics of LTES and the effects of the composite PCM with…”
Section: Introductionmentioning
confidence: 99%
“…Phase change materials (PCMs) have high latent heat capacity, thus they can store and release a significantly high amount of energy during phase transition at specific temperature. Latent heat thermal energy storage technology with PCMs is a promising way to improve the utilization rate of renewable energy, and ease the contradiction between energy supply and demand 1–5 . PCMs have many application potentials, such as continuous use of solar energy, waste heat recovery and utilization, cooling of electronics, mobilized thermal energy storage 6–14 .…”
Section: Introductionmentioning
confidence: 99%